Broadband tunable beam steering with a broadband and linear phase shifter. Issue 8 (August 2014) - Yoo, Hyoungsuk; Lee, Woo‐Seok; Lee, Se‐Hee; Park, Jonghoo; Kim, Hongjoon
ABSTRACT A broadband tunable phased array antenna system was fabricated using a broadband and linear phase shifter. For the frequency between 1.6 and 2.4 GHz, more than ±19° of beam steering was achieved with a 1 × 4 array. The main part of this system consists of a low loss, compact, linear tunable phase shifter which is implemented with left‐handed transmission line theory. For the same frequency range, the phase shifter showed less than 5.1 dB insertion loss for the whole 360° phase variation with ±21° of phase deviation from a linear line for the control voltages. By combining this phase shifter with a broadband quasi‐Yagi antenna, a broadband tunable phased array was fabricated. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1830–1832, 2014